Hubungan Aktivitas Fisik dan Obesitas Sentral dengan Komplikasi Ulkus Diabetik Penderita DM Tipe 2 di Wilayah Puskesmas Rowosari II - Sumayyah, Sumayyah; Wahab, Zulfachmi; Tursinawati, Yanuarita (Dinasti Research, 2025)
Physical activity is any body movement caused by the work of skeletal muscles and increases the expenditure of energy and energy. Central obesity is the accumulation of excessive fat that can interfere with health. One of the chronic complications of diabetes mellitus, namely the problem of lesions on the feet called diabetik ulcers is a condition where open wounds are found on the skin surface on the feet in DM patients due to nerve abnormalities and peripheral arterial vascular disorders which can be caused by lack of physical activity and obesity. The purpose of this study was to analyze the relationship between physical activity and central obesity with the incidence of diabetik ulcer complications in type 2 DM patients. Analytical observational research with a case control approach. The research subjects were type 2 DM patients at the Rowosari II Health Center. The research instrument used was the GPAQ questionnaire to measure physical activity, midline to measure central obesity. Samples were taken according to the exclusion and inclusion criteria. In the bivariate analysis using the chi-square test with a significant value if p <0.05. Type 2 DM patients with mild moderate physical activity will have an OR = 22,8 (95% CI 2,7-193,7) of having diabetik ulcers than those with strenuous activity (p=0,005). Meanwhile, type 2 DM patients with central obesity will have an OR =11 (95% CI 0,59-47,3) having diabetik ulcers than type 2 DM patients who do not have central obesity(p=0,025). Light-moderate physical activity and the presence of central obesity have a significant relationship with the occurrence of diabetik ulcers in patients with type 2 diabetes.